Output feedback-based adaptive fuzzy sliding mode control for seismic response reduction of base-isolated buildings. (July 2022) - Rahmani, Behrooz; Ziaiefar, Ali; Hashemi, Shamsedin
Abstract: In this research, a model-free control strategy for vibration suppression of base-isolated structures, which are excited by an earthquake, is investigated. For this purpose, the semi-active base isolated system including a magnetorheological ( MR ) damper is utilized. In this way, the displacement of the base isolator is measured by a linear variable differential transformer ( LVDT ). Accordingly, an adaptive fuzzy sliding mode observer is implemented to estimate the vector of state tracking error. This estimated vector is then employed by an adaptive fuzzy sliding mode control scheme to calculate the input voltage of the MR damper. The efficiency of the implemented model-free control strategy is studied by some numerical simulations. The advantages of the proposed controller can be summarized as its flexibility and robustness against disturbance rejection and model uncertainty. Highlights: The dynamics of the superstructure is considered as an unknown external disturbance on the base isolator dynamics. The control objective is recast to asymptotically stabilize the base isolator. Since, obtaining an accurate model for the base-isolated building is impossible, an adaptive fuzzy sliding mode controller ( AFSMC ), which is a model-free control strategy, is then implemented. Since the state vector of the plant cannot be measured easily, a model-free adaptive fuzzy sliding mode observer is applied. The same controller can be implemented for every building and earthquake.